2013
DOI: 10.1002/j.1556-6676.2013.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

CACREP Accreditation: A Solution to License Portability and Counselor Identity Problems

Abstract: A confluence of forces addressing counselor identity occurred with the 20/20: A Vision for the Future of Counseling initiative, the 2009 Standards of the Council for Accreditation of Counseling and Related Education Programs (CACREP), and the quest by the American Association of State Counseling Boards to establish license portability. This article provides a historical context for the profession's struggles with these issues, 1 state's experience, TRICARE's impact, and the role CACREP standards can play in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…However, this category seemed to apply to individuals who defaulted on an educational loan and only occurred in two states. As the counseling profession looks to reduce disparity in licensing laws for counselors (Mascari & Webber, 2013), more research looking at the behaviors of licensing boards in making decisions to investigate and act upon claims is needed. Additionally, some of the narratives indicated that licensing boards have a difficult time determining if an individual pursuing licensure may have had an ethical violation in another state.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this category seemed to apply to individuals who defaulted on an educational loan and only occurred in two states. As the counseling profession looks to reduce disparity in licensing laws for counselors (Mascari & Webber, 2013), more research looking at the behaviors of licensing boards in making decisions to investigate and act upon claims is needed. Additionally, some of the narratives indicated that licensing boards have a difficult time determining if an individual pursuing licensure may have had an ethical violation in another state.…”
Section: Discussionmentioning
confidence: 99%
“…We were only interested in those ethical violations and complaints that resulted in disciplinary actions during the time period of 2010 to 2014. We chose this time frame because we wanted to analyze the most recent trends of licensing boards from the time all states recognized counseling licensure (ACA, 2016; Mascari & Webber, 2013). At the time of data collection, we identified 2014 as the most recent year that licensing boards would have had time to review complaints and provide subsequent disciplinary actions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Credentialing is important to the legitimacy of the counseling profession and the professional stature of counselors (Kaplan et al, 2014). The aim of counselor credentialing is to protect the interests of the public through assuring counselor competence (Homrich, DeLorenzi, Bloom, & Godbee, 2014; Mascari & Webber, 2013; Miller et al, 2010). At the same time, credentials serve as the foundation for establishing expertise in the eyes of the public.…”
Section: Credentialing Of Counselorsmentioning
confidence: 99%